Genetic viability of small American bison (Bison bison) populations a century after reintroduction - Scheideman, Fayelynn Fox; Ekernas, L. Stefan; Swallow, John G. (Frontiers in Conservation Science, 2025)
Recovering species are often managed in small numbers, requiring management strategies that maintain genetic variation for long-term viability. Here, we evaluate the genetic outcomes of two restored American bison (Bison bison) populations 15 generations after its reintroduction as Colorado’s first wildlife reintroduction. After initial reintroduction in 1914 to Genesee park, the herd was split into two separate populations in 1938. To determine the genetic viability of the restored populations, we genotyped 36 individuals from both herds, analyzing 52 microsatellite markers to asses heterozygosity, allelic richness, inbreeding, and population structure. Both herds exhibit relatively high observed heterozygosity (Genesee: 0.775 sd = 0.183; Daniels: 0.781 sd = 0.178), high allelic richness (Genesee: 5.17 sd = 1.45; Daniels: 4.96 sd = 1.46), and negative FIS values (Genesee: -0.112 bootstraps = -0.158, -0.065; Daniels: -0.15, bootstraps = -0.191, -0.108), indicating a lack of inbreeding. Despite ongoing gene flow, the herds remain genetically distinct, as supported by pairwise FST (0.0354, bootstraps = 0.024, 0.046), Nei’s D (0.136), and AMOVA results (FST = 0.078, p = 0.001). STRUCTURE analysis further confirmed that the herds maintain genetic clustering despite some admixture. These results suggest that Denver Mountain Parks’ long-term management strategies – promoting controlled gene flow while preventing inbreeding – have been effective in maintaining genetic variation. Intentional individual movement between herds and introductions from external metapopulations have contributed to the long-term viability of these herds. This study highlights the success of small, intensively managed bison populations in maintaining genetic health over many generations and underscores the importance of gene flow strategies in wildlife restoration.